2010
DOI: 10.1177/1545968310376757
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects on Cortical Excitability and Motor Recovery Induced by Repeated Muscle Vibration in Chronic Stroke Patients

Abstract: rMV with PT may be used as a nonpharmacological intervention in the neurorehabilitation of mild to moderate hemiparesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
167
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(178 citation statements)
references
References 53 publications
8
167
0
3
Order By: Relevance
“…As a general finding, the stroke severity correlated with the CSE on the AH: the more severe the stroke, the less excitable the corticospinal tract. Earlier, the severity of stroke has been found to be closely related to the modulation of CSE, not only with the acute stage functional impairment but with the clinical outcome [18,31]. In the present study the FAC 6mo correlated with acute stage CSE on the AH.…”
Section: Discussionsupporting
confidence: 62%
“…As a general finding, the stroke severity correlated with the CSE on the AH: the more severe the stroke, the less excitable the corticospinal tract. Earlier, the severity of stroke has been found to be closely related to the modulation of CSE, not only with the acute stage functional impairment but with the clinical outcome [18,31]. In the present study the FAC 6mo correlated with acute stage CSE on the AH.…”
Section: Discussionsupporting
confidence: 62%
“…While other vibration paradigms have demonstrated efficacy such as repeated flexor carpi radialis and biceps brachii vibration in neurorehabilitation and motor recovery in stroke patients (Marconi et al 2011), further investigations must now focus on the effects on corticospinal excitability with chronic Achilles tendon vibration. For instance, long-term potentiation of corticospinal excitability would be beneficial in rehabilitation as a countermeasure to the reduced neural drive observed in early stages of immobilization (Duchateau 1995;Gondin et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Marconi et al reported that long-term application of vibratory stimulation to stroke patients with upper limb spasticity resulted in spasticity decrease and motor map areas increase, and emphasized the importance of long-term stimulation 10) . In the present study, tissue compliance at relaxation showed significant increases in 3 steps from 0.75 kg to 1.25 kg immediately after vibratory stimulation, and in 5 steps from 0.5 kg to 1.5 kg after vibratory stimulation for three weeks, indicating the importance of long-term stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects were recruited from among those who were at least six months after the onset of stroke, were grade 2 on the MAS, on which they showed a noticeable increase in spasticity but could move their elbow joint 10) , had no pathological findings in the musculoskeletal system of the elbow, could understand and follow the directions of the experimenter, and had no history of treatment with botulinum toxin, phenol, or alcohol injections. Each subject voluntarily consented to participation in this study.…”
Section: Subjectsmentioning
confidence: 99%